Don't betray future generations - Abd Razak, Dzulkifli (2005)
FOLLOWING the Prime Minister Datuk Seri Abdullah Ahmad Badawi's call for an education revolution in January 2003, and veteran educationist Tan Sri Murad Mohamad Noor recently using the analogy of changing to a new shirt to describe what the education system needs, another similar call was made last week. This time it came from no less than the DirectorGeneral of Unesco himself at the AsiaPacific Regional launch of the Decade of Education for Sustainable Development at Nagoya University, Japan, on June 28. Concurrently, Unesco together with the United Nation University organised a twoday international conference on "Sustaining the Future — Globalisation and Education for Sustainable Education". In his keynote address, he described the new challenge of integrating Education for Sustainable Development (EfSD) into the mainstream education system. Indeed, he regarded EfSD as the vehicle for educational change and mobilisation which is long overdue.